1989
DOI: 10.1677/joe.0.1220177
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 inhibits thyrotrophin-induced human thyroglobulin gene expression

Abstract: The regulation of thyroglobulin (Tg) and its specific mRNA by interleukin-1 (IL-1) in cultured human thyrocytes was investigated. Specific binding of 125I-labelled IL-1 on thyrocytes was confirmed by solid-phase binding assay. Thyrocytes dispersed from Graves' thyroid tissues were incubated with TSH with or without recombinant human IL-1. TSH stimulated Tg release from cultured human thyrocytes in a dose- and time-dependent manner. Both IL-1 alpha and beta inhibited TSH-induced Tg release at concentrations ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 33 publications
3
18
1
Order By: Relevance
“…There have been several reports that IL-1 has stimulatory or inhibitory effects on the growth of human thyroid carcinoma cell lines (Kimura et al 1992, Zeki et al 1993, Inokuchi et al 1995, Yip et al 1995, although it is believed to have an inhibitory effect on human thyroid-specific gene expression , Ashizawa et al 1989. In the present study, we confirmed that IL-1 has a stimulatory effect on the growth of NIM1 cells and an inhibitory effect on the growth of NPA cells.…”
Section: Discussionsupporting
confidence: 85%
“…There have been several reports that IL-1 has stimulatory or inhibitory effects on the growth of human thyroid carcinoma cell lines (Kimura et al 1992, Zeki et al 1993, Inokuchi et al 1995, Yip et al 1995, although it is believed to have an inhibitory effect on human thyroid-specific gene expression , Ashizawa et al 1989. In the present study, we confirmed that IL-1 has a stimulatory effect on the growth of NIM1 cells and an inhibitory effect on the growth of NPA cells.…”
Section: Discussionsupporting
confidence: 85%
“…TSH was rather inhibitory on the cytokine(s)-induced MCP-1 expression. In contrast, the expression of TG, a thyroid-specific protein, mRNA and protein was remarkably stimulated by TSH and this TSH-dependent up-regulation of TG expression was completely blocked by a co-administration of IL-I as reported previously [27]. Furthermore, over 95% of the cultured cells incubated with TSH alone were positively stained with anti-TG antibody (data not shown).…”
Section: Discussionsupporting
confidence: 72%
“…Unlike IFN␥, IL-1␤ did not impair TSH-induced Tg expression or DNA synthesis in WRT cells. These results differ somewhat from those reported in human cells, where IL-1␤ impaired Tg expression stimulated by TSH (39,40; reviewed in Ref. 41).…”
Section: Discussioncontrasting
confidence: 92%